Concept Mapping Techniques to Support Learning Activities in TK Az-Zahra, Kabupaten Karawang - Ambar Tri Hapsari; Selli Mariko; Aulia Ar Rakhman Awaludin; Nani Mulyani (Institut Teknologi Nasional, Bandung, 2022)
This Community Service (PKM) aims at analyzing teachers’ difficulties in making interesting concept maps in the learning process namely teachers’ lack of understanding of various applications for making concept maps of subject matter, teachers’ difficulties in writing mathematical symbols used in creating learning instruments, as well as inadequate quality in the process of implementing learning activities. This PKM is located at Az-Zahra Kindergarten, Karawang, West Java. Data were collected by means of observation, interviews, and Zoom. The method used by the PKM team to solve problems was to provide training activities on a scheduled basis for one semester. The material presented was the introduction to and use of Mind Map and Math Type application software. The results of this PKM for partners are teachers’ ability to create interesting concept maps and the improvement of learning activities in education units. While the output for the PKM team is the fulfillment of responsibility stated in the Tri Dharma that must be carried out by lecturers indicated by receiving certificate from a partner.